Defınıtıons From Belagat The Morality Of-Contents Sura Isra Verses İnfluence On Notification Quran - YILDIRIM, Hamza (Scientific Journal of Faculty of Theology, 2017)
The prophets have had the opportunity to tell them more effectively when they used the language of the society to which they were dispatched, in a way that they were able to use it in the form of a claim. The Prophet Muhammed, sent as a turning prophet whose Arab poetry is the top was educated in the Qur'an by his Quranic eloquence, as well as conveying his childhood to the tribe who speaks Arabic language in the most disadvantaged manner in that society, and has effectively communicated the Qur'anic message to his people. For this reason, in a period of twenty-three years, the people of the region have entered into Islamic religion with his guidance. Likewise, the Qur'an addresses the subjects to whom they can understand, and places the word in the mind of the subject in an effective manner in a different style. The place of morality is great in religious instruction. In the Qur'an, the majority of the moral principles coexist is the sutra of Islam. The rules of morality described in this passage are mostly the rules of the general rule, but also the principles of the preceding religious texts. The moral codes of this period are analyzed in the direction of the eloquence, and the influence of the narrative style and the word of the conversation are investigated. The moral content verses in Surah and the Ten Commandments in the Torah are compared in terms of content and style, and the influence of the Qur'anic revelation has been addressed in various ways. This study is an example in which the style of the verses containing morality differs from the ten commandments expressed in Torah and reveals the literary direction of the Qur'anic in terms of verse.